Optical tomography system for bubbles detection in liquid medium - Jamaludin, Juliza (2013)
Process tomography is widely used in industrial, medical diagnostic, chemical engineering and many more because this method is suitable for multiphase flow imaging and measurement system. Optical tomography is one of the most popular methods that had been used in tomography area because it has high resolution compare to other methods of tomography system. The main goal of this project is to build a new design of optical tomography system for bubbles detector using couple charge device linear sensor and laser diode. In this report it describes the objectives, problems encountered, and scopes of the project. Detail’s discussion about research, methodology and result for this project also carried out in this report. This project present a new orientation of sensor and detectors compared to the previous research in a way to obtain more precise and concise of image reconstruction. The characteristics and the advantages of sensor and detectors that had been used in optical tomography system for bubbles detection also discussed in detail based on the literature review.